Proteoma total e diferencial de gemas axilares da cultivar RB867515 de cana-de-açúcar em diferentes cortes - Maranho, Rone Charles (2017)
The sugar-energy sector plays an important role in the sustainability of energy and consumption resources, with sugarcane being the raw material for obtaining ethanol, sugar and energy. The current sugarcane cultivation system involves the initial planting called plant cane and successive regrowths (ratoons), where the cultivation is maintained in the average of six years and five cuts, in commercial crops. The productivity decrease is evident in the current system of cultivation and generally, it is not feasible to maintain the sugar cane after fifth cut. Extrinsic and intrinsic factors to sugarcane may be related to the productivity decrease, and the use of molecular tools such as proteomics, may contribute to the elucidation of the genetic and biochemical effects in plant response to external factors, such as cultural practices and edafoclimatic factors. The objective of this work was to know the effect of sugarcane cultivation on protein expression during the sugarcane cutting cycles, characterizing the total and differential proteome of axillary buds of the plant cane and fourth ratoon of the cultivar RB867515. The total proteins were extracted in triplicate by the modified TCA/acetone method for use in axillary sugarcane buds. Protein samples were submitted to denaturing polyacrylamide gel electrophoresis (SDS-PAGE) and stained with comassie blue. Each lane of the polyacrylamide gel was fractionated and treated for purification and isolation of the polypeptides. Tryptic digestion was performed on each fragment with subsequent UPLC separation (Nano Acquity). The polypeptides were analyzed on Waters® Micromass® ESI-Q-Tof micro ™ mass spectrometer. The adaptation of the protein extraction protocol, performed in the present work, was effective in the extraction of total proteins in 200 mg of plant material. Protein samples from the axillary buds at different cut stages showed distinct bands patterns in the SDS-PAGE gel if it was promising for the proteomic study. Two hundred thirty five proteins were identified, of which 71 were differentially expressed in the plant cane, 52 in the fourth ratoon and 112 were expressed in both cuts. The proteins identified are part of the most diverse cellular structures and/or participate in biological processes as a response to stresses, metabolism of carbohydrates, lipids and nucleic acids, regulation of gene expression, etc. Stand out in each cut, proteins related mainly to biotic and abiotic stresses, regulation of gene expression, transcription factors and signal transduction. Many important proteins detected in the plant cane, mainly those that participate in defense responses of the plants, were not found in the fourth ratoon (five cut). In the fourth ratoon, were highlighted a set of proteins that indicate the influence of abiotic and biotic stresses and conditions of anoxia and/or hypoxia on the axillary buds of this cut, even in axillary buds not submitted to these conditions. The differential proteome of the plant cane and fourth ratoon represents changes at the molecular level with great potential for a considerable productivity and longevity decrease, found in the ages of more advanced cuts in the cane fields.